Frequency of Fluid Overload and Usefulness of Bioimpedance in Patients Requiring Intensive Care for Sepsis Syndromes. Issue 1 (1st January 2016) - Larsen, Timothy R.; Singh, Gurbir; Velocci, Victor; Nasser, Mohamed; Mccullough, Peter A.
Abstract : Guideline-directed therapy for sepsis calls for early fluid resuscitation. Often patients receive large volumes of intravenous fluids. Bioimpedance vector analysis (BIVA) is a noninvasive technique useful for measuring total body water. In this prospective observational study, we enrolled 18 patients admitted to the intensive care unit for the treatment of sepsis syndromes. Laboratory data, clinical parameters, and BIVA were recorded daily. All but one patient experienced volume overload during the course of treatment. Two patients had >20 L of excess volume. Volume overload is clinically represented by tissue edema. Edema is not a benign condition, as it impairs tissue oxygenation, obstructs capillary blood flow, disrupts metabolite clearance, and alters cell-to-cell interactions. Specifically, volume overload has been shown to impair pulmonary, cardiac, and renal function. A positive fluid balance is a predictor of hospital mortality. As septic patients recover, volume excess should be aggressively treated with the use of targeted diuretics and renal replacement therapies if necessary.